EKSPERIMENTASI MODEL PEMBELAJARAN 4Ex2 DAN LC 5E PADA MATERI PLSV DAN PtLSV DITINJAU DARI SIKAP SISWA TERHADAP MATEMATIKA - Fitrianna, Aflich Yusnita; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the students attitude towards mathematics. The learning model compared were 4Ex2, LC 5E and conventional learning model. Data analysis techniques used to test the hypothesis was two-way analysis of variance with unbalanced cells. The conclusions of the research were as follows. 1) The learning achievement in Mathematics of the students exposed to the 4Ex2 learning model are better than LC 5E learning model and conventional learning model, andÂ  the learning achievement in Mathematics of the students exposed to the LC 5E learning model are better than conventional learning model. 2) The learning achievement in Mathematics of the students with the high attitudes toward Mathematics are better than that of the students with the medium and low attitudes toward Mathematics, and the learning achievement in Mathematics of the students with the medium attitudes toward Mathematics are better than that of the students with the low attitudes toward Mathematics. 3) In the 4Ex2 learning model, the learning achievement in Mathematics of the students with the high attitudes toward Mathematics are better than medium and low attitudes toward Mathematics, and the learning achievement in Mathematics of the students with the medium attitudes toward Mathematics are better than low attitudes toward Mathematics. In the LC 5E learning model, the learning achievement in Mathematics of the students with the high attitudes toward Mathematics are better than medium and low attitudes toward Mathematics, the learning achievement in Mathematics of the students with the medium attitudes toward Mathematics are the same as low attitudes toward Mathematics. In the conventional learning model, the learning achievement in Mathematics of the students with the high attitudes toward Mathematics are the same as medium attitudes toward Mathematics, the learning achievement in Mathematics of the students with the high and medium attitudes toward Mathematics are better than low attitudes toward Mathematics. 4) In the students with the high attitudes toward Mathematics the learning achivement of the students exposed to the LC 5E learning model are the same as 4Ex2 learning model and the conventional learning model, the learning achievement in Mathematics of the students exposed to the 4Ex2 learning model are better than conventional learning model, and both in the students with the medium attitudes toward Mathematics and in those with the low attitudes toward Mathematics, students exposed to the 4Ex2 learning model, LC 5E learning model, and conventional learning model result in the same learning achievement in Mathematics.Keywords: Learning model, 4Ex2, LC 5E, attitudes toward Mathematics, learning achievement in Mathematics.